1992
DOI: 10.1159/000261440
|View full text |Cite
|
Sign up to set email alerts
|

Mutans Streptococci and Lactobacilli in Breast-Fed Children with Rampant Caries

Abstract: This study aimed to investigate the prevalence of selected components of the oral microflora in breast-fed children who developed rampant caries (resembling nursing caries) under hitherto unexplained circumstances. Dental plaque and saliva samples were collected from breast-fed children, aged between 1 and 2.5 years, with and without rampant caries. Mutans streptococci and lactobacilli were isolated from dental plaque of all children with rampant caries and from most caries-free children. None of the colonies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
67
1
16

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 21 publications
11
67
1
16
Order By: Relevance
“…[22] and Aas et al [23], demonstrated that caries can occur in the absence of S. mutans. The results of these studies had similar results in which mutans was associated with both caries active and caries free children, contradicting its role in the initiation and progression of caries [24][25][26] In contrast, Carmona et al [9], found that the frequency of S. mutans was 76% in subjects with caries and 24% in subjects without caries showing a statistically significant difference. Ge et al [27], demonstrated that ECC is associated not only with increased levels of S. mutans but also due to elevated levels total streptococci in the mouth.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…[22] and Aas et al [23], demonstrated that caries can occur in the absence of S. mutans. The results of these studies had similar results in which mutans was associated with both caries active and caries free children, contradicting its role in the initiation and progression of caries [24][25][26] In contrast, Carmona et al [9], found that the frequency of S. mutans was 76% in subjects with caries and 24% in subjects without caries showing a statistically significant difference. Ge et al [27], demonstrated that ECC is associated not only with increased levels of S. mutans but also due to elevated levels total streptococci in the mouth.…”
Section: Discussionmentioning
confidence: 92%
“…S. mutans is a dominating species, widespread in populations with low caries prevalence, indicating that the ecological determinants of these bacteria are not necessarily associated with a caries promoting lifestyle [28]. Matee et al [24] and Sullivan et al [25], observed that the level of oral streptococci in the saliva of children cannot predict future caries. The importance of S. mutans in caries etiology has been well documented, but the growing recognition that the cariogenic potential may be determined by complex interactions in dental plaque biofilm rather than solely the virulence properties of a single organism [29] hence, there was no clear relationship between caries experience and the presence of S. mutans.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that ad libitum breast-feeding during sleep resulted in higher MS counts in dental plaque and more dental caries among young children 9,13) . Other factors associated with this Dental Caries and Prolonged Breast-feeding high caries incidence may be the cariogenic potential of human milk and the tendency to eat other more cariogenic food 6) .…”
Section: Discussionmentioning
confidence: 95%
“…[10,33] However, some recent studies indicate that the relationship between S. mutans, and caries is not absolute high proportions of S. mutans may persist on tooth surfaces without lesion development, and caries can develop in the complete absence of S. mutans. [34,35] Veillonella are an acidogenic Firmicutes with 5.8% of the total population. In this study, 5 patients showed complete absence of this genus in the deep layer.…”
Section: Discussionmentioning
confidence: 99%